Comparative evaluation of clinical and radiographical outcomes of immediate versus delayed dental implant placement: A prospective study - Ashish Bali; Mrinal Jindal; Amit Goel; Virshali Gupta; Ankita Dadwal; Shiva Chauhan (Wolters Kluwer Medknow Publications, 2019)
Background: To investigate the crestal bone changes following immediate versus delayed dental implant placement. Aims and Objective: Comparative evaluation of clinical and radiographical outcomes of immediate versus delayed dental implant placement: A prospective study. Methods: A prospective randomized comparative study was conducted in total of ten implant sites in patients within the age group of 20 to 60 years comprising both male and female visiting the Out-Patient Department of Periodontics, Himachal Dental College, Sunder Nagar (H.P.). Clinical parameters were recorded at baseline (1 month), 3 months and 6 months; they included Probing depth (PD), Radiographic Assessment (RA) for crestal bone changes. Results: On intergroup comparison, the mean difference of the probing between Group I and Group II showed that Group I had slightly higher probing depth [Table 1] than Group II during 1st to 3rd month and 3rd to 6th month period and On intergroup comparison, the mean difference of the crestal bone changes [Table 2] between Group I and Group II showed that Group II had slightly higher bone loss than Group I during 1st to 3rd month and 3rd to 6th month period. Conclusion: Within limitations of this study, it can be concluded that there was significant crestal bone loss in Group II (delayed implantation) at both mesial and distal surface during 3rd to 6th month's observation period. Furthermore, a continuous bone resorption was observed over the time in both the groups. Due to small sample size, short duration, and two-dimensional radiographical assessment of crestal bone loss during follow-up in the study, long-term survival of two-piece implants in both the groups cannot be determined; so, further studies are required to be done.